The use of various materials as a metal component in a metamaterial thermophotovoltaic emitter - Yasnohorodskyi, M.A. (Radiotekhnika, 2022)
Thermophotovoltaics (TPV) is a process by which photons emitted by a heat emitter are converted into electrical energy by a photovoltaic cell. Selective heat emitters that can survive temperatures at or above 1000°C have the potential to significantly improve the energy conversion efficiency of a PV cell by limiting the emission of photons with energies below the band gap energy of a photovoltaic cell. Waste heat can be a valuable source of energy if we can find a way to harvest it efficiently. Deviations from ideal absorption and ideal blackbody behavior lead to light losses. For selective emitters, any light emitted at wavelengths outside the bandgap energy of the photovoltaic system may not be efficiently converted, reducing efficiency. In particular, it is difficult to avoid emission associated with phonon resonance for wavelengths in the deep infrared, which cannot be practically converted. An ideal emitter would not emit light at wavelengths other than the bandgap energy, and much TFP research is devoted to designing emitters that approximate better this narrow emission spectrum. TPV systems usually consist of a heat source, a radiator and a waste heat removal system. TFV cells are placed between the emitter, often a metal or similar block, and the cooling system, often a passive radiator. Efficiency, heat resistance and cost are the three main factors for choosing a TPF emitter. The efficiency is determined by the absorbed energy relative to the incoming radiation. High temperature operation is critical because efficiency increases with operating temperature. As the temperature of the emitter increases, the radiation of the black body shifts toward shorter waves, which allows for more efficient absorption by photocells. This paper demonstrates the feasibility of using materials such as platinum, gold, and nichrome as a metal component in a metamaterial emitter with respect to their absorption and thermal stability.